Prediction of Packed Cell Volume after Whole Blood Transfusion in Small Ruminants and South American Camelids: 80 Cases (2006–2016). (29th September 2017) - Luethy, D.; Stefanovski, D.; Salber, R.; Sweeney, R.W.
Abstract : Background: Calculation of desired whole blood transfusion volume relies on an estimate of an animal's circulating blood volume, generally accepted to be 0.08 L/kg or 8% of the animal's body weight in kilograms. Objective: To use packed cell volume before and after whole blood transfusion to evaluate the accuracy of a commonly used equation to predict packed cell volume after transfusion in small ruminants and South American camelids; to determine the nature and frequency of adverse transfusion reactions in small ruminants and camelids after whole blood transfusion. Animals: Fifty‐eight small ruminants and 22 alpacas that received whole blood transfusions for anemia. Methods: Retrospective case series; medical record review for small ruminants and camelids that received whole blood transfusions during hospitalization. Results: Mean volume of distribution of blood as a fraction of body weight in sheep (0.075 L/kg, 7.5% BW) and goats (0.076 L/kg, 7.6% BW) differed significantly ( P  < 0.01) from alpacas (0.103 L/kg, 10.3% BW). Mild transfusion reactions were noted in 16% of transfusions. Conclusions and Clinical Relevance: The generally accepted value of 8% for circulating blood volume (volume of distribution of blood) is adequate for calculation of transfusion volumes; however, use of the species‐specific circulating blood volume can improve calculation of transfusion volume to predict and achieve desired packed cell volume. The incidence of transfusion reactions in small ruminants and camelids is low.